Analysis the possibility of improving the economic indicators of exploitation the deposit Cementacija Kraku Bugaresku - Ore field Cerovo - Vaduvesković Zoran; Vušović Nenad; Kržanović Daniel (Mining and Metallurgy Engineering Bor, 2014)
Cementacija - Kraku Bugaresku is a complex of ore bodies in the southeastern part of the deposit Cerovo. It contains a substantial portion of ore with high content of oxides regarding to the total copper in the ore, and with the existing processing technology in the current period, the modest results in metal recovery were achieved. This work, through an analysis, gives a discussion of possible combination of processing using the conventional flotation processing with pyrometallurgical treatment and heap leaching with the hydrometallurgical extraction of metal by SX -EW, in terms of the economic viability of such method. This work firstly made a comparison of optimization results of potential open pits in the ore deposit (Whittle Fx), in both cases for the same input techno-economic data. The obtained potential open pits in the optimization process (pit shells) for Revenue Factor 1 (i.e. the selling price of Cu cathode ton of 5,000 $) are differ from each other by about 8 million tons of ore in favor of the combined processing method and the amount of Cu in the ore to 16,502.44 t, while had grade in the case of method combination is higher for 3.27 %. Discounted cash flow is higher by as much as 61.94 %, which expressed in monetary units is 47,905,712$.